Supporting Refugees and Host Communities in East Africa - Regional Durable Solutions Secretariat (ReDSS) (Regional Durable Solutions Secretariat (ReDSS), 2017)
Displacement in Eastern Africa is predominantly of a protracted nature. At the end of May 2017, there were almost 13 million people displaced in the region- with 4 million refugees mostly from South Sudan and Somalia, and at least half are children. More than one million children have fled escalating violence in South Sudan, so almost one in five children. The vast majority of refugees have been hosted in neighboring countries for decades. Uganda for instance is currently hosting 1.2 million refugees making it the largest refugee-hosting country in Africa. Uganda has welcomed more refugees in the last month of 2016 than the total number of refugees and migrants crossing the Mediterranean into Europe in the entire year.